Bird Species Diversity in the Padawan Limestone Area, Sarawak - Mohammad Saiful Mansor,; Shahrul Anuar Mohd Sah,; Lim Chan Koon ,; Mustafa Abdul Rahman, (Tropical Life Sciences Research, 2011)
Bird surveys were conducted in the Padawan Limestone Area for seven days at each of two study sites, Giam and Danu, from August to December 2008. The purpose of the study was to compare the area’s bird species richness and abundance of bird species in other limestone areas and in other forest types. The study also compared the species richness and relative abundance of birds in undisturbed and disturbed areas at both study sites. Twenty mist nets were deployed for 12 hours daily. During this study period, direct observations of birds were also made. In all, 80 species from 34 families were recorded at both sites. At Giam, 120 birds were mist-netted. These birds represented 31 species from 16 families. The direct observations at Giam recorded 13 species from 11 families. In the undisturbed area, 21 species from 13 families were mist-netted, whereas in the disturbed area, 21 species from 10 families were mist-netted. In Danu, a total of 48 birds, representing 25 species from 12 families, were mist-netted. The observations at Danu recorded 34 species from 19 families. Twelve species from 7 families were mist-netted in the undisturbed area, whereas 18 species from 11 families were mist-netted in the disturbed area. Statistical analysis showed that the species diversity index differed significantly between undisturbed and disturbed areas. Kajian burung telah dilakukan di kawasan batu kapur Padawan selama tujuh hari di setiap dua lokasi kajian, Giam dan Danu, dari Ogos hingga Disember 2008. Tujuan kajian adalah untuk membandingkan kekayaan dan taburan spesis-spesis burung antara kawasan ini dan kawasan batu kapur yang lain, dan juga jenis-jenis hutan yang lain. Kajian ini juga membandingkan kekayaan spesis dan taburan relatif burung-burung di kawasan tidak terganggu dan kawasan terganggu di kedua-dua lokasi kajian. Dua puluh jaring kabut telah dipasang selama 12 jam sehari. Pemerhatian langsung juga telah dijalankan. Sejumlah 80 spesis daripada 34 famili telah direkod di kedua-dua lokasi kajian. Di Giam, 120 burung telah ditangkap. Burung-burung ini mewakili 31 spesis daripada 16 famili. Pemerhatian langsung di Giam merekod 13 spesis daripada 11 famili. Di kawasan tidak terganggu, 21 spesis daripada 13 famili telah ditangkap, manakala di kawasan terganggu, 21 spesis daripada 10 famili telah ditangkap. Di Danu, sejumlah 48 burung, mewakili 25 spesis daripada 12 famili telah ditangkap. Pemerhatian di Danu telah merekod 34 spesis daripada 19 famili. Dua belas spesis daripada 7 famili telah ditangkap di kawasan tidak terganggu, manakala 18 spesis daripada 11 famili telah ditangkap di kawasan terganggu. Analisis statistik menunjukkan bahawa indeks kepelbagaian spesis berbeza secara signifikan antara kawasan tidak terganggu dan terganggu.